Training on making rice straw-based compost for farmer group in Prafi District, Manokwari Regency - Budi Santoso; Bambang Tjahyono Hariadi; Daniel Yohanes Seseray (University of Merdeka Malang, 2022)
Farmers in Prafi District often experience problems with the availability of inorganic fertilizers, so it is necessary to provide organic fertilizer. The objectives were to provide insight into the role of environmentally friendly fertilizers for soil and plants, to transfer knowledge and technology for composting based on rice straw waste, and to assist farmers in Prafi District, in overcoming the problem of scarcity and high prices of fertilizers. This training was held in Aimasi Village, Prafi District, attended by 24 members of the Harapan Makmur group and Petani Peternak Terpadu Sebelas group. The training included the preparation of materials, counseling, and practice, application of compost to plants, and evaluation. The results of the activity showed that the participants gave an excellent response to the introduction of composting technology made from a mixture of rice straw and cow feces. Farmers could make compost, so there was no need to buy fertilizers used for planting vegetables and fruits. Moisture content, organic matter, C-total, and N-total of rice straw-based compost were within the criteria of SNI compost. It was concluded that most of the farmers had understood the material provided and had been able to independently make compost with good quality.